Solving Higher Order Ordinary Differential Equation with Initial Condition using Differential Transform Method - JAAFAR, NUR AZIRA; ABD LATIF, NOOR AZLIZA (Enhanced Knowledge in Sciences and Technology, 2023)
In this study, higher order ordinary differential equation (ODE) with initial conditions have been solved by using differential transform method (DTM). DTM is a semi-analytic numerical method for solving differential equations. Some examples are solved numerically, and the results are compared with Adaptive Polynomial Method (APM), Modification of Adomian Decomposition Method (MADM), Laplace Transform Method (LTM) and the exact solution. Maple 2021 have been used to solve the higher order equation. The obtained results are shown in tables and graph to show that the DTM is more accurate compared to the others method.